SISTEM INFORMASI PENJUALAN DAN PEMBELIAN PADA TOKO BERKAH JAYA PUTRA MENGGUNAKAN VB.NET - Fadhila, Salma; Paryati, Retno (Jurnal Mahasiswa Terapan, 2024)
This study aims to analyze, design, implement, and test the sales and purchase information system at Toko Berkah Jaya Putra. The method used in this research is a descriptive method with a qualitative approach, describing the actual situation that is happening, while the analysis method used is PIECES analysis and using the waterfall system development method. The data collection methods used are observation, interviews, and literature studies. The next stage is the design of Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), normalization, menu structure, and interface design. Using Visual Studio 2010 programming language and MySQL as a database. Testing using black box testing. The results of the research are a sales and purchase system application. System testing can meet functional needs in accordance with the design made. This system has the ability to record sales and purchase transactions in a computerized manner, which makes the calculation process and report generation more efficient and effective, with its function the system can solve problems related to recording transactions, calculations and uncontrolled item data, which can be overcome by the information system that has been created.